Dual inhibition of ERG11 and CDR2 in drug-resistant Candida albicans by Indian phytochemicals: a combined in silico–in vitro approach - Mundhe, Akshay Kisan; Rajkumari, Reena (Frontiers in Pharmacology, 2026)
Invasive candidiasis caused by drug-resistant Candida albicans is an escalating global health concern due to the declining efficacy of conventional antifungal therapies. In this study, Indian medicinal phytochemicals were investigated as potential dual inhibitors of the key resistance determinants ERG11 (lanosterol 14α-demethylase) and CDR2 (efflux protein Candida drug resistance 2) of C. albicans using a combined in silico–in vitro approach. Structure-based virtual screening of 17,967 phytochemicals from the IMPPAT (Indian Medicinal Plants, Phytochemistry and Therapeutics) database identified eleven high-affinity candidates. Five lead compounds—dalspinin-7-O-β-D-galactopyranoside, glycyrol, isokurarinone, licoflavone A, and liquiritin—exhibited strong binding toward ERG11 (−9.2 to −9.5 kcal/mol), outperforming fluconazole (−7.3 kcal/mol). Except for isokurarinone, all compounds also demonstrated effective binding to CDR2, indicating dual-target potential. Molecular dynamics simulations (100 ns) confirmed the structural stability of ERG11–ligand complexes, with liquiritin and glycyrol showing the most persistent interactions. Phytochemicals were experimentally confirmed from Glycyrrhiza glabra extracts using HR-LCMS and exhibited concentration-dependent antifungal activity against multiple drug-resistant Candida and non-Candida yeast pathogens in vitro. Collectively, these findings demonstrate the promising antifungal potential of Indian phytochemicals as dual ERG11–CDR2 inhibitors. These results provide a strong basis for developing phytochemical-based antifungal leads for future therapeutic applications.